2022
DOI: 10.3389/fimmu.2022.1005426
|View full text |Cite
|
Sign up to set email alerts
|

Improving the immunomodulatory function of mesenchymal stem cells by defined chemical approach

Abstract: Mesenchymal stem cell (MSC) is a potential therapeutic material that has self-renewal, multilineage differentiation, and immunomodulation properties. However, the biological function of MSCs may decline due to the influence of donor differences and the in vitro expansion environment, which hinders the advancement of MSC-based clinical therapy. Here, we investigated a method for improving the immunomodulatory function of MSCs with the help of small-molecule compounds, A-83-01, CHIR99021, and Y27632 (ACY). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…MSCs inhibit T cell functions by producing immunosuppressive factors and by direct cell–cell contacts. The soluble mediators produced by MSCs are TGF-β, prostaglandin E 2 (PGE 2 ), indoleamine 2,3-dioxygenase (IDO), IL-10, and nitric oxide, all of which inhibit the activation of inflammatory leukocytes 11 . MSCs also increase the proliferation and functions of Tregs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs inhibit T cell functions by producing immunosuppressive factors and by direct cell–cell contacts. The soluble mediators produced by MSCs are TGF-β, prostaglandin E 2 (PGE 2 ), indoleamine 2,3-dioxygenase (IDO), IL-10, and nitric oxide, all of which inhibit the activation of inflammatory leukocytes 11 . MSCs also increase the proliferation and functions of Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs also increase the proliferation and functions of Tregs. Overall, these properties of MSCs make them good candidates for the treatment of SLE 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In the process of organ development, disease, repair, and regeneration, the cell density in tissues changes greatly [ 9 ]. Studies have shown that the change in cell density has biological significance.…”
Section: Introductionmentioning
confidence: 99%